Soil Damage Control Techniques Based on Local Wisdom in Sumberbrantas Village, Batu City - Febriani, Yenni; Santosa, Langgeng Wahyu; Harini, Rika (Journal of Geosciences and Environmental Studies, 2025)
Sumberbrantas village faces potential soil damage due to agricultural intensification for biomass production on sloping land with high erosion rates. The importance of soil conservation through the local wisdom approach encourages this research to explore soil damage control techniques the local community applies. This study aims to identify local wisdom-based soil conservation techniques applied in land management for biomass production. The methods used included structured interviews with 90 respondents who work as farmers/gardeners, followed by field observations and documentation to collect primary data on community characteristics, land use, and conservation techniques. The results showed that the community applied conservation techniques in crop rotation, intercropping, and terracing as the primary efforts to reduce soil damage. Organic fertilizers, simple technologies such as hoeing, mechanical methods in the form of rolling terraces, and vegetative methods in the form of ground cover plants are also commonly applied. Most communities have gained this knowledge from generation to generation and through regular counseling. Land management based on community wisdom in Sumberbrantas Village effectively maintains land productivity while preserving the environment. These techniques reflect the community's adaptation to environmental challenges, with the potential to be further developed through modern innovations and local traditions.